Ministry of Trade and Industry Decree No. 512 of the Year 2013 Concerning the Termination of Protection Against the Substantial Increase in the Raw and White Sugar Imports Without Imposing Final Charges = وزارة التجارة والصناعة قرار رقم 512 لسنة 2013 بشأن إنهاء تحقيق الوقاية ضد الزيادة الكبيرة فى الواردات من صنف السكر الخام والأبيض دون فرض رسوم نهائية - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.